PENERAPAN MEDIA PAPAN PERKALIAN DALAM MENGATASI KESULITAN BELAJAR BERHITUNG PERKALIAN KELAS 3 - Eka Agustin Wulandari; Zaeni, Abu (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2024)
The problem experienced by 3rd grade students of MI Islamiyah Banjaranyar during the learning process is difficulty in calculating multiplication. This study aims to find out the difficulties of multiplication counting and the explanation of the application of multiplication board media in overcoming students' difficulties in multiplication calculation and to find out the supporting factors for the use of multiplication board media for grade 3 students of MI Isalamiyah Banjaranyar. This researcher is designed using a qualitative approach. The data collection techniques in this study include observation, interviews, and documentation. The results of the findings found that there were 5 students who had difficulty calculating multiplication. Based on the results of the study, it can be concluded that (1) to overcome the difficulty of multiplication calculation, educators use multiplication board media. The implementation steps are to introduce the multiplication board media to the students, face the multiplication board media, the teacher explains KI, KD and the learning objectives, the teacher explains the multiplication material, the teacher explains how to use the multiplication board, then the teacher asks the students to try to calculate multiplication by using the multiplication board media. (2) The factors that support the existence of multiplication board media are clear visuals, interaction, teacher creativity, institutional support, interaction and can be manipulated. Another factor is the existence of a learning place, support from the principal to apply this multiplication board media and from the results of the application of this multiplication board media, the difficulty of calculating multiplication is resolved. (3) factors that affect the inhibition of multiplication board media in overcoming students' difficulties in learning to multiply are Limited Access, Teacher Readiness, Student Interest, Inconsistent Application. Lack of Interaction, Separation from Real Context.